Preoperative thrombocytopenia as a predictor of cancer-associated thromboembolism in gastric cancer patients undergoing gastrectomy - Jung, Moonki; Park, Song Ee; Choi, Jin Hwa; Kim, Jeong Eun; Hwang, In Gyu (Frontiers in Oncology, 2025)
PurposeCancer-associated thromboembolism (CAT) is a major complication in gastric cancer, impacting patient outcomes. This study aimed to evaluate preoperative thrombocytopenia as a risk factor for CAT in gastric cancer patients undergoing gastrectomy.Materials and methodsA retrospective analysis was conducted on 610 gastric cancer patients who underwent D2 gastrectomy between 2005 and 2017. The incidence of CAT and its association with preoperative thrombocytopenia, cancer stage, and recurrence were analyzed. Prognostic factors for CAT and survival were assessed using Kaplan-Meier analysis and Cox regression models.ResultsThe median follow-up was 67.0 months. Among the study participants, 5.7% (n=35) developed CAT. Preoperative thrombocytopenia was present in 71 patients (11.6%) and older age (≥65 years) was noted in 308 patients (50.1%). The 5-year incidence rate of CAT was 16.3% in patients with preoperative thrombocytopenia, compared to 4.8% in those with normal platelet counts. Patients with preoperative thrombocytopenia had a higher incidence of CAT compared to those with normal platelet counts (HR = 3.180, 95% CI 1.527-6.623, p = 0.002). Multivariate analysis revealed that thrombocytopenia (HR = 2.202, 95% CI 1.029-4.711, p = 0.042), older age (HR 2.484, 95% CI 1.166-5.290, p = 0.018), stage IV (HR = 2.966, 95% CI 1.106-8.466, p = 0.038) were independent poor prognostic factors for preoperative CAT in gastric cancer patients. Additionally, 29.7% of patients experienced cancer relapse, and 26.1% died during post-treatment follow-up. the patients who developed thromboembolisms had a significantly shorter 5-year OS rate compared with those who did not (56.6% vs. 76.1%, HR = 2.277, 95% CI = 1.376–3.767, p = 0.001).ConclusionsPreoperative thrombocytopenia is a significant predictor of CAT in gastric cancer patients. Along with advanced stage and older age, it increases thromboembolic risk and worsens survival. Further studies are needed to refine predictive models and optimize management strategies.